Molecular and Cellular Mechanisms of Preeclampsia - Huppertz, Berthold (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on the "Molecular and Cellular Mechanisms of Preeclampsia" belongs to the section "Molecular Pathology, Diagnostics, and Therapeutics" of the International Journal of Molecular Sciences. It was a very successful Special Issue as it contains 20 published papers, including one editorial, nine original research papers, and ten reviews on the topic. The original publications cover a wide spectrum of topics, including alterations and involvement of specific factors during preeclampsia, new non-invasive technologies to identify changes, new treatment options, animal models, gender aspects, and effects of the pregnancy pathology later in life. The review publications again cover a wide spectrum of topics, including factors and pathways involved in preeclampsia, effects on the maternal vascular and immune systems, effects on the placenta and the trophoblast, epigenetic changes, new preventive strategies, and new views on the current hypotheses on preeclampsia. Taken together, this Special Issue gives a fantastic overview on a broad spectrum of topics, all of which are important to identify the real etiology of preeclampsia and to finally develop real treatment options.